Relationship Between Social Motivation in Children With Autism Spectrum Disorder and Their Parents - Uljarević, Mirko; Frazier, Thomas W.; Jo, Booil; Phillips, Jennifer M.; Billingham, Wesley; Cooper, Matthew N.; Hardan, Antonio Y. (Frontiers in Neuroscience, 2021)
Impairment in social motivation (SM) has been suggested as a key mechanism underlying social communication deficits observed in autism spectrum disorder (ASD). However, the factors accounting for variability in SM remain poorly described and understood. The current study aimed to characterize the relationship between parental and proband SM. Data from 2,759 children with ASD (Mage = 9.03 years, SDage = 3.57, 375 females) and their parents from the Simons Simplex Collection (SSC) project was included in this study. Parental and proband SM was assessed using previously identified item sets from the Social Responsiveness Scale (SRS). Children who had parents with low SM scores (less impairments) showed significantly lower impairments in SM compared to children who had either one or both parents with elevated SM scores. No parent-of-origin effect was identified. No significant interactions were found involving proband sex or intellectual disability (ID) status (presence/absence of ID) with paternal or maternal SM. This study establishes that low SM in children with ASD may be driven, in part, by lower SM in one or both parents. Future investigations should utilize larger family pedigrees, including simplex and multiplex families, evaluate other measures of SM, and include other related, yet distinct constructs, such as social inhibition and anhedonia. This will help to gain finer-grained insights into the factors and mechanisms accounting for individual differences in sociability among typically developing children as well as those with, or at risk, for developing ASD.